Az Első Pécsi Bőrgyár Részvénytársaság a zsidótörvények korában (1938–1945) - Schweitzer, Gábor; Vörös, István Károly (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
The paper intends to present what consequences had the anti-Jewish laws and other measures in Hungary adopted from 1938 have, for one of the largest companies of the city of Pécs at the time, the First Leather Factory Plc. in Pécs. The overview, which also contains results from archival research, covers the following topics: 1) the role of the First Leather Factory Plc. in Pécs on the economic life of the city, with particular regard to the work of Sándor Róth, the company’s general manager; 2) the impact of the so-called 2nd Anti-Jewish Law (Act IV of 1939) on the employees of the leather factory; 3) The lay-offs of 1944; 4) the registration of ‘Jewish’ shareholders in 1944; 5) victims of the Shoah among the employees of the leather factory.